Non-invasive treatment of skin problems - Tribulaitė, Martina; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2022)
With age the structure of facial skin changes. Non-invasive procedures help maintain skin’s elasticity, the need for them exists in the 21st century too.Aim. Was to ascertain the effect of non-invasive procedures on facial skin problems.Research Methods. A qualitative investigation and oral survey were chosen. Two participants were chosen in the targeted selection: participant 1 (28 years old) was treated with the Darsonval apparatus; ultrasound procedures were chosen for participant 2 (56 years old).Results and Conlusions. Following the procedures, the number of acnes decreased on both sides of the face of participant 1, sebum secretion was partly regulated, a network of capillaries on the cheeks diminished visually, the condition of facial skin improved. The expected results were partly achieved.As to participant 2, mimic wrinkles, fine lines around the eyes and deeper wrinkles in the T zone were slightly reduced. Minimum results were achieved: a feeling of skin tension was removed, skin became softer, smoother, keratinisation reduced. Frequency of non-invasive procedures enabled the participants with skin problems to reach a positive result of skin changes, which was achieved faster in the case of participant 2.
Keywords: skin problems; non-invasine procedures; skin treatment